Analysis of Leverage, Cash Ratio, Net Profit Margin Towards Dividend Payout Ratio in Manufacturing Companies in the Metal Sub Sector and That Listed on the Indonesia Stock Exchange for the 2016-2020 Period - Feronika Perangin-angin; Anggi Pratama Nasution; Puja Rizqy Ramadhan (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study aims to find empirical evidence of Leverage, Cash Ratio and Net Profit Margin to Dividend Payout Ratio in metal and similar sub-sector manufacturing companies listed on the IDX. The period used in this study is 5 (five) years, starting from 2016-2020. The population used in this study amounted to 16 companies. The sampling technique used was purposive sampling method, and 11 companies were used as samples. The data analysis technique used is multiple linear regression analysis. The results of the study found that: partially (1) Leverage has a positive and significant effect on the Dividend Payout Ratio (2) the cash ratio has a positive and significant effect on the Dividend Payout Ratio (3) Net profit margin has no effect on the Dividend Payout Ratio.